Tajikistan Country Economic Update, Fall 2020 : Economic Slowdown Amid the Pandemic - World Bank (World Bank, Washington, DC, 2021)
The COVID-19 pandemic had a significant adverse impact on the Tajik economy. Real GDP growth slowed to 4.2 percent year-on-year in the first nine months of 2020, compared to 7.2 percent a year earlier. Restrictions on labor mobility and economic activity at home and abroad resulted in lower migrant remittances, weaker consumer demand, and reduced investments. Although exports enjoyed a record global demand for gold, the domestic market collapsed, suggesting a more severe impact of COVID-19 on domestic jobs and incomes. A growing share of the population reported reducing their food consumption, and the inability of previously returned migrants to travel abroad led to a significant increase in the unemployment rate. The healthcare system faces unprecedented pressure to accommodate a sudden influx of patients. International financial institutions and partner countries rushed with financial and in-kind aid to help Tajikistan contain the pandemic’s impact. In an effort to ameliorate the economic fallout, the authorities deferred tax collections, boosted health and social spending, and eased monetary policy. They established an interagency task force to address health challenges emerging from the pandemic.